Data forwarding mechanism based on dynamical coding nodes managing for intermittent connectivity wireless network - Da-peng WU; Peng-wen LOU; Si-long FAN; Ru-yan WANG (Tongxin xuebao)
The limited network resources can be utilized effectively by the network coding method in intermittent connectivity wireless network, but the number of coding nodes should be dynamically adjusted according to network status. To effectively improving the network resources utilization, a data forwarding mechanism based on dynamically managing coding nodes for intermittent connectivity wireless network was proposed. According to the estimated results of current network status, the optimal number of required coding nodes could be determined with the distributed manner. Further-more, the social property and available resources were considered for coding nodes selecting to achieve reliable data forwarding with the lower overhead. Results show that the connection opportunities between nodes can be exploited adequately by our mechanism; moreover, the utilization of network resources can be improved dramatically.